Dynamical Behavior of the Stochastic Delay Mutualism System - Peiyan Xia; Daqing Jiang; Xiaoyue Li (Abstract and Applied Analysis)
We discuss the dynamical behavior of the stochastic delay three-specie mutualism system. We develop the technique for stochastic differential equations to deal with the asymptotic property. Using it we obtain the existence of the unique positive solution, the asymptotic properties, and the nonpersistence. Finally, we give the numerical examinations to illustrate our results.